The spinning voltage influence on the growth of zno-rgo nanorods for photocatalytic degradation of methyl orange dye - Ramos P.G. (2020)
In this work, well-designed zinc oxide-reduced graphene oxide (ZnO-rGO) nanorods (NRs) were synthesized by a hydrothermal method using electrospun ZnO-rGO seed layers. The ZnO-rGO seed layers were fabricated on fluorine-doped tin oxide (FTO) glass substrates through calcined of electrospun nanofibers at 400◦C in the air for 1 h. The nanofibers were prepared by electrospinning different spinning voltages and a spinning solution containing zinc acetate, polyvinyl pyrrolidone, and 0.2 wt% rGO. From a detailed characterization using various analytical techniques, for instance, X-ray diffraction (XRD), field emission scanning electron microscopy (SEM), Raman spectroscopy, photoluminescence (PL), and X-ray photoelectron spectroscopy (XPS), the dependence of the structure, morphology, and optical properties of the ZnO-rGO NRs was demonstrated. The photocatalytic activities of ZnO-rGO nanorods were evaluated through the degradation of dye methyl orange (MO). The results show that the change of spinning voltages and the coupling of rGO with ZnO improved photodecomposition efficiency as compared to pure ZnO. The highest photocatalytic efficiency was obtained for the ZnO-rGO NRs prepared with a spinning voltage of 40 kV.